1225 Christmas Tree Lane - Macomber, Debbie (Don Mills, Ont. : Mira, 2011)
"The people of Cedar Cove know how to celebrate Christmas. Like Grace and Olivia and everyone else, Beth Morehouse expects this Christmas to be one of her best. Her small Christmas tree farm is prospering, her daughters and her dogs are happy and well, and her new relationship with local vet Ted Reynolds is showing plenty of romantic promise. But-- someone recently left a basket filled with puppies on her doorstep, puppies she's determined to place in good homes. That's complication number one. And number two is that her daughters Bailey and Sophie have invited their dad, Beth's long-divorced husband, Kent, to Cedar Cove for Christmas. The girls have visions of a mom-and-dad reunion dancing in their heads. As always in life--and in Cedar Cove--there are surprises, too. More than one family's going to have a puppy under the tree. More than one scheme will go awry. And more than one romance will have a happy ending!" -- from author's web site.
97929
Keywords: Divorced mothers; Mothers and daughters; Man-woman relationships; Cedar Cove (Wash. : Imaginary place); Christmas stories